2020
DOI: 10.1177/1524838020957983
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Confinement of Inmates Associated With Relapse Into Any Recidivism Including Violent Crime: A Systematic Review and Meta-Analysis

Abstract: Recidivism among released inmates is associated with a substantial societal burden given the financial and medical consequences of victimization. Among incarcerated North Americans, approximately 7% are housed in solitary confinement (SC). Studies show SC can lead to psychological deterioration and dispute it can effectively reduce institutional misconduct or recidivism. This meta-analysis aims to clarify the impact of SC on postrelease recidivism, which we hypothesized would increase following SC. A meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 93 publications
0
14
1
Order By: Relevance
“…Finally, the second mortality study found a significant increase for homicide specifically (hazard ratio of 1.54) ( 17 ). Because exposure to SC also seems to increase the risk of committing violence post-release ( 74 ), it is plausible that releasees also could be at risk of mortality in such altercations. Still, this is the first meta-analytical investigation of mortality following SC and more than two studies are required to further evaluate mortality outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the second mortality study found a significant increase for homicide specifically (hazard ratio of 1.54) ( 17 ). Because exposure to SC also seems to increase the risk of committing violence post-release ( 74 ), it is plausible that releasees also could be at risk of mortality in such altercations. Still, this is the first meta-analytical investigation of mortality following SC and more than two studies are required to further evaluate mortality outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…At the forefront of this literature is research demonstrating that, after controlling for factors related to rule violations and recidivism (e.g., age, criminal history, misconduct history), the severity and frequency of exposure to sanctions increases difficulties reentering society, in turn increasing the likelihood of recidivism (Butler et al, 2020; Camp & Gaes, 2005; Gaes & Camp, 2009; Silver & Nedelec, 2018). For example, inmates exposed to solitary confinement recidivate at higher rates in comparison to inmates who remain in the general population (Butler et al, 2020; Luigi et al, 2020). Moreover, Cochran and Mears (2017) used group-based trajectories to assess the relationship between prison misconduct and recidivism.…”
Section: Prison Sanctionsmentioning
confidence: 99%
“…The existing literature has examined the timing of disciplinary segregation but not the timing of any sanctions including but not limited to segregation (Butler et al, 2020; Clark & Duwe, 2019; Lovell et al, 2007). To illustrate the dearth of research, a recent meta-analysis conducted by Luigi et al (2020) identified only four studies that examined how timing of solitary confinement affected the recidivism rates of inmates. This meta-analysis revealed that the odds of recidivism were higher when inmates were housed in solitary confinement closer to their release.…”
Section: Prison Sanctionsmentioning
confidence: 99%
See 2 more Smart Citations